The Relationship Between Arm Length and Arm Muscle Power with the Chest Pass Ability - Pajar Juanda; Iyakrus; Ahmad Richard Victorian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The aim of this study is to determine whether there is a relationship between arm length, arm muscle power, and chest pass ability among male students in the basketball extracurricular program at Muara Pinang 1 Public Senior High School. This research is designed using a correlational research design. It is a population study involving all male students participating in the basketball extracurricular program at Muara Pinang 1 Public Senior High School, totaling 30 individuals. Data collection techniques include testing, and data analysis is performed using correlation tests. The results of data processing and analysis indicate a strong correlation between arm length and chest pass ability (r = 0.87), as well as between arm muscle power and chest pass ability (r = 0.87). The findings suggest a highly significant relationship between arm length, arm muscle power, and chest pass ability among male students in the basketball extracurricular program at Muara Pinang 1 Public Senior High School, with a correlation coefficient of 0.93.